Thyrotoxicosis with primary presentation as dysphagia: a rare manifestation - Banday, Tanveer H.; Bhat, Sadaf Bashir; Kmat, Ashwin; Bhat, Shashikantha; Nanjundswamy, Mathuraja (International Journal of Research in Medical Sciences, 2017)
Thyrotoxicosis refers to the clinical manifestations associated with elevated serum levels of T4 or T3 in an individual. Dysphagia is a common problem but a rare manifestation of hyperthyroidism. Dysphagia is an uncommon manifestation of thyrotoxic myopathy. Reports have been sparse and its incidence is not clear. In our case report patient presented who with dysphagia and weight loss and investigation revealed hyperthyroidism. Patient dysphagia subsequently resolved after receiving treatment with methimazole and beta-blockers. This case report the need to include thyrotoxicosis in the differential diagnosis of an otherwise unexplained case of dysphagia.